ANTIOXIDANT ACTIVITY AND PHYSICO-CHEMICAL PROPERTIES OF GREEN SYNTHESIZED ZINC OXIDE NANOPARTICLES USING ERUCA SATIVA LEAF EXTRACT - Mohammed, Lina Y. (Science Journal of University of Zakho, 2023)
The aim of this work is to synthesize zinc oxide (ZnO) nanoparticles from Eurca Sativa water extract which is a medicinal plant cultivated in home gardens in Kurdistan Region-Iraq. The biosynthesis of nanoparticles has been extensively studied due to their numerous applications. Among them, zinc oxide nanoparticles (ZnO NPs) have gained significant attention for wide range of its applications. To investigate the optical, chemical, structural, and morphological properties, different techniques; UV-VIS spectrophotometer, Fourier Transform Infrared Analysis (FT-IR), X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), Energy-dispersive X-ray spectroscopy (EDX) were used. The results revealed that typical ZnO absorption spectra exhibit a well-defined exciton band at 371.6 nm that is near the bulk exciton absorption of ZnO (373 nm) with an energy band gap of 3.029 eV, confirming the production of ZnO nanoparticles. FTIR study demonstrated the existence of bioactive compounds such as flavonoids, polyphenols, tannins, and saponins that can function as reducing and capping agents of ZnO nanoparticles. FESEM picture revealed that ZnO NPs show spherical morphologies with an average diameter of 71.07 nm. The antioxidant activities of biosynthetic ZnO NPs were studied using non-enzymatic methods; 2,2-diphenyl-1-picrylhydrazyl (DPPH), reducing power assay, and total antioxidant activities. The results showed that the biosynthesized ZnO-NPs nanoparticles had significant antioxidants compared with ascorbic acid as a reference. The obtained results showed that the present method is eco-friendly, less cost-effective, and safe for human health and this method plays a vital role in the industrial and biomedicine fields.